2007
DOI: 10.1200/jco.2006.08.0283
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 Guanine/Adenine 870 Polymorphism With Altered Protein Expression Is Associated With Genomic Instability and Aggressive Clinical Biology of Esophageal Adenocarcinoma

Abstract: Our data suggest that CD1 A870 background may be imparting aggressive phenotype to EAC. It provides a molecular basis to explain the clinical biology associated with CD1 polymorphism whereas aberrant nuclear accumulation of CD1 protein enhances the acquisition of genomic instability (ie, clonal diversity), thus leading to early age of EAC diagnosis and poor OS. CD1 genotyping with other biomarkers may help create a biomarker-based prognostic model for EAC and CD1 may also serve as a therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…The polymorphism of 807 G/A increases the frequency of alternate splicing, leading to an altered protein that does not contain the sequences involved in protein turnover and may have a longer half-life (Betticher et al, 1995). However, different studies indicate that the polymorphism might not be involved in the predisposition to ESCC (Yu et al, 2003;Liu et al, 2010), whereas some other show contrasting results (Izzo et al, 2005(Izzo et al, , 2007. Other genetic variations of cell cycle related proteins, such as retinoblastoma and p21, which interact with CCND1, were found.…”
Section: Discussionmentioning
confidence: 98%
“…The polymorphism of 807 G/A increases the frequency of alternate splicing, leading to an altered protein that does not contain the sequences involved in protein turnover and may have a longer half-life (Betticher et al, 1995). However, different studies indicate that the polymorphism might not be involved in the predisposition to ESCC (Yu et al, 2003;Liu et al, 2010), whereas some other show contrasting results (Izzo et al, 2005(Izzo et al, , 2007. Other genetic variations of cell cycle related proteins, such as retinoblastoma and p21, which interact with CCND1, were found.…”
Section: Discussionmentioning
confidence: 98%
“…However, the oncogenic alternatively spliced isoform of cyclin D1 lacks the phosphorylation site and remains nuclear (32), showing that at some stage, cancer cells can overcome the inhibition of DNA synthesis by cyclin D1. Remarkably, it was recently shown that in human esophageal adenocarcinoma, the appearance of this alternatively spliced cyclin D1 isoform was associated with increased genomic instability (52). Previously, it was shown that cyclin D1 overexpression induces centrosome and mitotic spindle abnormalities, as well as aneuploidy in murine hepatocytes in vivo and in human breast epithelial cells in vitro (53).…”
Section: Discussionmentioning
confidence: 99%
“…This novel correlation requires verification in other patient populations with EAC, particularly in other races, because our population was overwhelmingly Caucasian. EGF genotyping may thus eventually form one of a panel of molecular markers that includes p53 expression status (29) and cyclin D1 (30,31) that is clinically useful in predicting which GERD patients should have increased surveillance endoscopy. Although these molecular markers are not yet applicable in clinical practice, the EGF A61G polymorphism may be among the first markers that may identify EAC risk, with particular interest in women, nonobese individuals, and early-onset EAC, where few risk factors (either clinical or molecular) have been identified.…”
Section: Discussionmentioning
confidence: 99%